Pengembangan Media Pembelajaran Puzzle Untuk Meningkatkan Keterampilan Menulis pada Pembelajaran Bahasa Indonesia Materi Teks Deskriptif di Sekolah Dasar - Indriani, Novi; Yanti, Prima Gusti (CV. ITTC INDONESIA, 2024)
This research aims to develop learning media in the form of Puzzles to improve writing skills and find out the suitability of Puzzle media in class IV Indonesian language learning at Muhammmadiyah Cibinong Elementary School which is valid and practical for use in learning activities. The research method is R & D (Research and development), with the ADDIE development model used analysis, design, development, implementation and evaluation. Based on the results of research analysis obtained from material experts, they obtained a score of 88% in the